Análise numérica não-linear da flambagem local de perfis de aço estrutural submetidos à compressão uniaxial - Ana Lydia Reis de Castro e Silva (2006)
Local buckling of plates normally presents large displacements in the normal direction of the medium plane of the plate due to small loading changes, with the axis of the bar remaining straight. This is a typical phenomenon of axially compressed steel columns, composed either with welded or hot- rolled structural shapes. When the plate buckles locally, there is a change in the original stress distribution in the medium plane of the buckled plate and an increase in the strength, called post-buckling strength. The postbuckling strength behaviour is affected by many nonlinear influence parameters, such as plate slenderness, initial geometric imperfections, residual stresses and nonlinear material behaviour. In this work, it was developed a theoretical and numerical study, using the nonlinear analysis software ABAQUS, in order to comprehend the local buckling nonlinear behaviour of structural I shapes and structural angles of axially compressed steel columns. First the fundamentals of the local buckling and the basis of the formulation of the Revision of the Brazilian Standard for the Design of Steel Structures PR NBR 8800 (2006) was described. Subsequently, several analysis of platestability and local buckling of sections were performed. It was adopted a methodology for the implementation and analysis starting from simple cases found in the literature and gradually adding the nonlinear influence parameters. This approach allowed the understanding and validation of the results, showing good numerical agreement in the comparisons and also the expected behaviour in the analysis. The strength curves of thestudied profiles were obtained as a function of the slenderness of their component elements and were compared to the Brazilian Standard curves. The results showed a valid approach for the problem, contributing to the characterization of the behaviour of these structural steel profiles under the local buckling phenomenon, and allowed to question the procedures of the PR NBR 8800 (2006). Some relevant issues pointed inthis study are: (i) the influence of the residual stresses, especially for thin plates; (ii) the differences introduced by the approximation of the section behaviour by the observation of the isolated plates behaviour; (iii) the simplifications and errors in the Brazilian Standard formulation of post-buckling resistance of structural angles; (iv) the confusions in the Brazilian Standard strength curves of structural I shapes with slenderwebs; and (v) the lack of accuracy in the Brazilian Standard by the disregarding of the structural welded I shapes composed by cut- flame plates.